Systematic analysis and investigations on different coil structures with misalignments for WPT system - B. Annaselvaraj; P. Srinivasa Rao Nayak; K. Sundareswaran; Sishaj P. Simon (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
The wireless power transfer (WPT) has gained popularity in the recent days for charging of various portable electronic gadgets such as robotic vacuum cleaners, pacemakers and also mobile phones. WPT is also largely employed for charging of electric vehicles. For a WPT system, two major components are transmitter and receiver which are mutually coupled together for power transfer. Here, the transmitter coil is positioned statically while the receiver coil is placed in the electronic gadget or in the electric vehicle. The structures of coupling coils are generally of circular, square and rectangular arrangements. The transmitter and receiver coils could be ideally completely aligned or misaligned depending upon the designed structures. The mutual inductance (MI) between the transmitter and receiver coils is a vital parameter which decides the wireless power transfer efficiency and for different coil structures. Hence, this parameter needed to be investigated for different coil structures with and without perfect alignment. This paper makes an attempt to compute the MI for different coil structures with and without perfect alignments employing Finite Element Method (FEM). For comparison, a prototype system was developed in the laboratory and the computed MI values are compared with measured values and there is a good correspondence between the two are observed. Further, the MI is measured for different arrangements and presented in this paper. It is observed that the MI of WPT system decreases with displacement between the two coils as well as the quantum of misalignment. Furthermore, square coil arrangement with perfect and various misalignment leads to higher MI.